Jakimi językami mówili chrześcijanie w Afryce Prokonsularnej? Analiza odnośnych tekstów Tertuliana, św. Cypriana i św. Augustyna - Turek, Waldemar Jan (Vox Patrum, 2019)
The study has focused on the languages used by Christians in Proconsular Africa. Since they derived primarily from three cultural backgrounds (Phoenician, Greek and Latin), first of all, it tries to ascertain how many of them spoke Phoenician (strictly speaking: Punic), Greek or Latin. It turns out that in the studied time period, from the III to V centuries, the Roman circles furthered their own language and culture and they did this very effectively. As a result, more and more Christians in the region used Latin, and in consequence most of the literary production (even that which originally had been in Punic and Greek) survived in the Latin version. Furthermore, it is noted that it was thanks to the Christians of Proconsular Africa, and not of Rome, that in time Latin became the major language of the Church. As the respective texts of Tertullian, St. Cyprian and St. Augustine are compared, it becomes clear that there were three different styles of Latin used by these Christians. First of all, there was the polished language, in which the authors continued the style of writing based on ancient classical Latin (even though they introduced changes as to the meaning and terminology used). These same authors, in many cases, in particular in catechesis and preaching used a simpler Latin, taking into account the perceptive capacities of the simple faithful. The poorest Latin was used by those who were brought up in the lowest strata, particularly in the Phoenician society.